2019
DOI: 10.1016/j.yjmcc.2019.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Requisite roles of LOX-1, JNK, and arginase in diabetes-induced endothelial vasodilator dysfunction of porcine coronary arterioles

Abstract: Diabetes is associated with cardiac inflammation and impaired endothelium-dependent coronary vasodilation, but molecular mechanisms involved in this dysfunction remain unclear. We examined contributions of inflammatory molecules lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1), stress-activated kinases (c-Jun N-terminal kinase [JNK] and p38), arginase, and reactive oxygen species to coronary arteriolar dysfunction in a porcine model of type 1 diabetes. Coronary arterioles were isolated from stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…38 We also performed functional studies with coronary and retinal arterioles isolated from the same diabetic pigs, but surprisingly found that TEMPOL only restored NOS-mediated dilation of coronary arterioles. 39 Our findings from this previous work with coronary arterioles also suggest that upregulation of arginase I in these vessels leads to the production of superoxide. These disparate results related to the roles of superoxide and arginase in retinal and coronary arterioles underscore the apparent heterogeneity in mechanisms of diabetes-induced endothelial vasodilator dysfunction in the microcirculation.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…38 We also performed functional studies with coronary and retinal arterioles isolated from the same diabetic pigs, but surprisingly found that TEMPOL only restored NOS-mediated dilation of coronary arterioles. 39 Our findings from this previous work with coronary arterioles also suggest that upregulation of arginase I in these vessels leads to the production of superoxide. These disparate results related to the roles of superoxide and arginase in retinal and coronary arterioles underscore the apparent heterogeneity in mechanisms of diabetes-induced endothelial vasodilator dysfunction in the microcirculation.…”
Section: Discussionmentioning
confidence: 59%
“…For some vessels, the relationship between NOS and arginase in the vasodilations to histamine and bradykinin was evaluated in the presence of L-NAME with or without the arginase inhibitor nor-NOHA (0.1 mmol/L intraluminal treatment for 90 minutes; Cayman Chemical; Ann Arbor, MI, USA). 28,39 To assess the involvement of arginase and superoxide in the diabetes-induced effect, the vasodilator responses were examined after intraluminal treatment of vessels with nor-NOHA (0.1 mM) 28,39 or superoxide dismutase mimetic TEMPOL (1 mmol/L), 38,39 respectively, for 90 minutes.…”
Section: Study Of Vasomotor Functionmentioning
confidence: 99%
“…This finding is consistent with a previous study showing that PKCβ2 activation links to the impairment of flow-induced vasodilation in a microvascular network by suppression of NO release from the endothelium [ 52 ]. Interestingly, inhibition of PKCβ2 preserves endothelium-dependent vasodilation [ 53 ] and reverses endothelial barrier dysfunction [ 54 ] in experimental models with hyperglycemia and diabetes, which are known to cause endothelial NO deficiency [ 14 , 23 , 52 , 55 ]. It should be noted that PKCβ2 is expressed abundantly in the coronary arteriolar wall, including endothelial cells, and is co-localized with eNOS ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inhibition of PKC has been shown to attenuate vascular superoxide production in various forms of cardiovascular stress in animals [14,17,18] and humans [14,19]. Interestingly, recent studies suggested a role of mitogen-activated protein kinases (MAPKs) or Rho kinase in superoxide production from coronary microvessels subjected to inflammatory insults [20][21][22] or harvested from animals with cardiovascular diseases [21,23,24]. However, it remains unclear whether direct activation of PKC signaling in the healthy vasculature can cause MAPK/Rho kinase activation and excessive superoxide production, with consequent vasomotor dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, only a few JNK inhibitors have been tested in clinical trials for various indications, yet none for the treatment of cardiovascular pathology. Preclinical studies on the use of JNK-specific inhibitors such as AS601245 and SP600125 have been found to exert cardiovascular protective effects by attenuating cardiac inflammation, endothelial dysfunction, as well as protecting against diabetic nephropathy progression [ 205 , 206 , 207 ].…”
Section: Pkc-mapk As Therapeutic Target For Cardiovascular Management...mentioning
confidence: 99%